INTERNATIONAL GUIDELINES ON PERIOPERATIVE MANAGEMENT OF GLP-1 RECEPTOR AGONISTS: A NARRATIVE REVIEW - Karol Grela; Aleksandra Grygorowicz; Klaudia Baran; Michał Ględa; Michał Szyszka; Weronika Radecka; Weronika Kozak; Agnieszka Szreiber; Karolina Nowacka; Kamil Jabłoński; Anna Woźniak; Kornelia Rynkiewicz (International Journal of Innovative Technologies in Social Science, 2025)
Background: The widespread use of glucagon-like peptide-1 receptor agonists (GLP-1 RAs) in the treatment of diabetes mellitus and obesity has led to a growing number of patients receiving these agents presenting for surgical and procedural interventions. Their known effects on gastric motility have raised concerns regarding delayed gastric emptying and perioperative aspiration risk, prompting the publication of multiple professional society recommendations. Objectives: This review aims to identify, compare, and critically analyse contemporary clinical practice guidelines addressing the perioperative management of patients treated with GLP-1 receptor agonists, with particular focus on drug continuation versus withholding, risk stratification, and mitigation strategies. Methods: A narrative review of professional society guidelines published between 2020 and 2025 was conducted. A structured bibliographic database search and citation analysis identified official recommendations from anaesthesiology, diabetology, gastroenterology, and perioperative medicine societies. Guidelines were analysed with respect to recommendations on perioperative GLP-1 RA management, identification of high-risk patients, proposed risk mitigation strategies, and supporting evidence. Results: Substantial heterogeneity was observed among guidelines. While early recommendations favoured routine discontinuation of GLP-1 RAs, more recent guidance supports an individualised, risk-based approach. Commonly identified risk factors include early treatment phase, dose escalation, higher doses, gastrointestinal symptoms, and comorbid conditions affecting gastric motility. Proposed mitigation strategies include dietary modification, selective drug withholding, gastric point-of-care ultrasound, and tailored anaesthetic techniques. Most recommendations are based on low-quality evidence and expert opinion. Conclusions: Current guidance increasingly favours personalised perioperative management of GLP-1 RA–treated patients. High-quality prospective studies are needed to better define perioperative risk and inform evidence-based, harmonised recommendations.